ASSESSMENT OF THE ORAL HEALTH RISK FACTORS IN YOUNG PEOPLE - Alice Murariu; Doriana Agop Forna; Florentina Manolache; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2017)
The aim of our study is to identify the risk factors involved in oral health in a group of students from 2 universities in Iasi with different profile, medical and non-medical and to highlight the cases with inappropriate health behavior. Material and methods: A cross-sectional survey was conducted in 2016 and was selected a sample of 110 students from University of Medicine and Pharmacy "Grigore T. Popa" (UMF) and University "Al.I.Cuza" (UAIC) of Iasi. The risk factors were assessed with a questionnaire with 12 questions divided in two sections: first section-dietary habits concerning sweet foods, carbonated drinks, fruits and vegetables consumption and oral hygiene, and other risk factors for oral health such as: smoking, alcohol consumption and dental check-ups, in second section. Results: There were no differences between students, regarding the consumption of cariogenic food, 28.8% students from UMF, compared to 29.9% students from UAIC. The daily drinking of carbonated drinks is an unhealthy habit among 3.4% of medical students and 7.8% non-medical young people. Regarding oral hygiene, there are more students from medical university who used mouthwash, 55.6% versus 43.5% and also for brushing after each meal, 13.3% compared to 3.9%. No significant differences were observed between groups for alcohol consumption, dental check-ups and the reasons for seeing a dentist. Conclusions: The knowledge and attitudes towards healthy life is not high correlated with the medical profile, because life style depends also on the family behavior, friends' influences and educational role of the universities. This study highlights the importance of educational courses for health in university curriculum.